Coastal Community Development in Gender and Development Perspective: Study of Women's Empowerment in the Kenjaran Area of Surabaya - Windiani; Soedarso; Suryani, Adi; Setyaningsih, Yuni; Fatthatin, Bazighoh; Aprilinda, Khusnul A; Febrianti, Puput R. (Indonesian Journal of Development Studies, 2022)
Gender Equality is one of the main targets of the Sustainable Development Goals (SDGs). For this reason, the complexity of problems in community development, especially women's empowerment, is an important dimension that needs to be analyzed in the context of achieving the SDGs. This research explores and analyzes how the Gender and Development perspective is used in developing coastal communities, especially in women's empowerment programs in the coastal area of Kenjeran, Surabaya City. The research used a qualitative method with a participatory rural appraisal (PRA) approach. Data collection was carried out using participant observation and focus group discussion techniques. The informants in this study were actors involved in the development and empowerment of women in the Kenjeran area of Surabaya, which were taken purposively according to the research objectives. The results of this study can become a reference and database in community development with a Gender and Development perspective. The research results provide policy recommendations, especially for development planners and stakeholders involved in developing coastal communities and empowering women in various regions in Indonesia. In particular, research has found development and empowerment models that can be used as databases and models in developing sustainable development programs.